Membrane permeability-guided identification of neuroprotective components from Polygonum cuspidatun. (March 2014) - Xiao, Hai-tao; Qi, Xiao-lan; Liang, Yan; Lin, Cheng-yuan; Wang, Xia; Guan, Zhi-zhong; Hao, Xiao-yan
Abstract Context: Polygonum cuspidatum Sieb et Zucc. (Polygonaceae) possesses various pharmacological activities and has been widely using as one of the most popular and valuable Chinese herbal medicines in clinics. Its usage has increasingly attracted much of our attention and urges investigation on its bioactive components. Objective: To establish a rapid and valid approach for screening potential neuroprotective components from P. cuspidatum. Materials and methods: Potential neuroprotective components from P. cuspidatum were screened utilizing liposome equilibrium dialysis followed by high-performance liquid chromatography (HPLC) analysis. Their neuroprotective effects on modulation of protein expression of α7 nAChR, α3 nAChR and synaptophysin (SPY) on SH-SY5Y human neuroblastoma cell line (SH-SY5Y) were evaluated by means of Western blotting. Results: Two potential compounds, polydatin (C1) and emodin-8-O-β-d-glucoside (C2), were detected and identified in our study. The biological tests showed that both compounds C1 and C2, respectively, at concentrations of 0.1 and 0.25 mg/mL significantly increased protein expression of α7 and α3 nicotinic acetylcholine receptors (nAChRs) in SH-SY5Y cells. Moreover, C1 and C2 at 0.1 mg/mL significantly reversed the Aβ1-42-induced decrease of α7 and α3 nAChRs protein expression in SH-SY5Y cells. In addition, C2 at 0.1 mg/mL significantly increased protein expression of SPY in SH-SY5Y cells and Aβ1-42-induced SH-SY5Y cells whereas C1 did not provide any positive effects. Discussion and conclusion: In conclusion, our approach utilizing liposome equilibrium dialysis combined with HPLC analysis and cell-based assays is a prompt and useful method for screening neuroprotective agents.